+0  
 
0
37
1
avatar+21 

A)     7(x-2)-3(x+3)=5(x-3)=x

 

 

B)      9-6(x-1)=2(x-4)+27

 

C) 5x+12=87

 

D)   3 fourths x -5=4 

 

E) - fraction 5 over 2 x divided by 6=1 

 

F) 6x+3=-1

kminery62  Sep 24, 2018

Best Answer 

 #1
avatar
+1

Hello kminery62. The way you worded some of the problems was confusing, but I tried my best.

 

For question B:

9 - 6(x - 1) = 2(x - 4) + 27

9 - 6x + 6 = 2x - 8 +27          Distribute.

-8x = 4                               Move similar terms to the same side.

x = -2                                 Divide.

 

For question C:

5x + 12 = 87

5x = 75                               Subtract.

x = 15                                Divide.

 

For question D: 

(3/4)x - 5 = 4

(3/4)x = 9                            Add.

(1/4)x = 3                            Divide.

x = 12                                Multiply.

 

For question E:

(-5/2)x / 6 = 1

(-5/2)x = 6                           Multiply.

(1/2)x = -6/5                        Divide.

x = -12/5                             Multiply.

x = -2 1/5                            Simplify.

 

For question F:

6x + 3 = -1

6x = -4                                Subtract.

x = -4/6                               Divide.

x = -2/3                               Simplify.

Guest Sep 24, 2018
 #1
avatar
+1
Best Answer

Hello kminery62. The way you worded some of the problems was confusing, but I tried my best.

 

For question B:

9 - 6(x - 1) = 2(x - 4) + 27

9 - 6x + 6 = 2x - 8 +27          Distribute.

-8x = 4                               Move similar terms to the same side.

x = -2                                 Divide.

 

For question C:

5x + 12 = 87

5x = 75                               Subtract.

x = 15                                Divide.

 

For question D: 

(3/4)x - 5 = 4

(3/4)x = 9                            Add.

(1/4)x = 3                            Divide.

x = 12                                Multiply.

 

For question E:

(-5/2)x / 6 = 1

(-5/2)x = 6                           Multiply.

(1/2)x = -6/5                        Divide.

x = -12/5                             Multiply.

x = -2 1/5                            Simplify.

 

For question F:

6x + 3 = -1

6x = -4                                Subtract.

x = -4/6                               Divide.

x = -2/3                               Simplify.

Guest Sep 24, 2018

9 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.